Evaluasi Program Supervisi Akademik Pengawas Madrasah dalam Upaya Meningkatkan Kompetensi Profesional Guru Madrasah Aliyah - Aos Kuswandi; Yeti Sulfiati; Ibnu Muthi (JAMP : Jurnal Administrasi dan Manajemen Pendidikan, 2022)
Abstract: This research aims to evaluate the academic supervision program of Madrasah Aliyah supervisors in improving the professional competency of teachers in North Bekasi District. The academic supervision program aims to build and assess teacher competency in terms of administration and teaching teacher skills. This research is an evaluation study with context, input, process, product (CIPP) model. This study used CIPP evaluation model. The data were collected using interview, observation and documentation techniques. The analysis techniques used are triangulation of data and sources. The subject of the study was madrasah supervisor, the principal and teachers of Madrasah Aliyah in North Bekasi District. The results showed: (1) The supervision program can assess teacher performance and professional competence of teachers from the administrative side, (2) Academic supervision program produces 2 products namely teacher performance assessment and follow-up program, (3) teachers can improve their competencies independently facilitated by madrasah supervisor and the principal of Madrasah Aliyah, (4) Academic supervision program can be continued with various improvements to improve the competency of Madrasah Aliyah teachers in North Bekasi District.Keywords : Program Evaluation, Academic Supervision, Professional CompetenceAbstrak: Penelitian ini bertujuan mengevaluasi program supervisi akademik pengawas Madrasah Aliyah yang secara context, input, process dan product dalam meningkatkan kompetensi professional guru di Bekasi Utara. Program supervisi akademik pengawas untuk membina dan menilai kompetensi guru  dari sisi administrasi dan kemampuan guru mengajar. Penelitian ini merupakan penelitian evaluasi dengan model Context, Input, Process, Product (CIPP). Pengumpulan data menggunakan teknik, observasi, wawancara dan dokumentasi. Teknik analisis yang digunakan adalah triangulasi data dan sumber. Teknik pengumpulan data dilakukan melalui wawancara, observasi, dan studi dokumentasi. Subjek penelitian adalah pengawas madrasah, Kepala Madrasah Aliyah, pengawas madrasah di Kecamatan Bekasi Utara. Hasil penelitian menunjukkan: (1) Program supervisi dapat menilai kinerja guru dan kompetensi professional guru dari sisi administratif, (2) Program supervisi akademik menghasilkan 2 produk yaitu penilaian kinerja guru dan program tindak lanjut, (3) guru dapat meningkatkan kompetensinya secara mandiri yang difasilitasi oleh pengawas madrasah dan Kepala Madrasah, (4) Program supervisi akademik dapat dilanjutkan dengan berbagai perbaikan untuk meningkatkan kompetensi guru Madrasah Aliyah di Kecamatan Bekasi Utara.Kata Kunci: Evaluasi Program, Supervisi Akademik, Kompetensi Profesional